2002
DOI: 10.1128/iai.70.7.3673-3680.2002
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Induction of Enterocyte Apoptosis byGiardia lambliaDisrupts Epithelial Barrier Function in a Caspase-3-Dependent Manner

Abstract: We recently demonstrated that Giardia lamblia rearranges cytoskeletal proteins and reduces transepithelial electrical resistance. The effect of G. lamblia on enterocyte apoptosis is unknown, and a possible link between microbially induced enterocyte apoptosis and altered epithelial permeability has yet to be established. The aim of this study was to assess whether G. lamblia induces enterocyte apoptosis in duodenal epithelial monolayers and whether this effect increases epithelial permeability. Monolayers of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
221
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(242 citation statements)
references
References 55 publications
10
221
2
9
Order By: Relevance
“…Recently several cysteine-type proteases of G. lamblia origin were detected after co-incubations with rat small intestine epithelial cells [15], and other host cell-Giardia interaction experiments and giardiasis patient data have shown that Giardia reduces the epithelial barrier function [16,17] and induces apoptosis [14,[21][22][23], but the effector protein(s) have never been identified. To improve our understanding of host-parasite interactions during infection, we asked whether exposure of G. lamblia to human intestinal epithelial cells (IEC) might lead to release of trophozoite proteins into the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Recently several cysteine-type proteases of G. lamblia origin were detected after co-incubations with rat small intestine epithelial cells [15], and other host cell-Giardia interaction experiments and giardiasis patient data have shown that Giardia reduces the epithelial barrier function [16,17] and induces apoptosis [14,[21][22][23], but the effector protein(s) have never been identified. To improve our understanding of host-parasite interactions during infection, we asked whether exposure of G. lamblia to human intestinal epithelial cells (IEC) might lead to release of trophozoite proteins into the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Giardia duodenalis strain NF was obtained from an epidemic outbreak of human giardiasis in Newfoundland, Canada (Chin et al, 2002). Giardia duodenalis trophozoites were grown axenically at 37 ° C in Diamond's TYI-S33 media supplemented with piperacillin (Piprecil; Wyeth-Ayerst Canada Inc., Montreal, Que., Canada) in 15 ml polystyrene centrifuge tubes (Falcon, Becton-Dickinson and Co., Franklin Lakes, NJ) and sub-cultured every 7 days to maintain the line.…”
Section: Giardia Productsmentioning
confidence: 99%
“…High concentrations of bacterial lipopolysaccharide (LPS) may also increase epithelial apoptosis and intestinal permeability ( [Yu et al, 2005], [Yu et al, 2006] and [Chin et al, 2006]). While it has been established that G. duodenalis-induced intestinal permeability defects require caspase-3 activation and appear to be strain-dependent ( and [Chin et al, 2002]), the mechanisms responsible for G. duodenalis-induced epithelial apoptosis remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 It should be noted that certain gastrointestinal pathogens, such as the parasite Giardia lambia, are known to modulate epithelial permeability through the induction of apoptosis. 51,52 As mentioned before, EPEC induces apoptosis in infected IECs in a caspase-dependent manner. 53,54 Nevertheless, recent studies concluded that the increase in epithelial permeability caused by EPEC is caspase-independent, as the inhibition of different initiator and executioner caspases did not restore the epithelial barrier properties.…”
Section: Disruption Of Epithelial Barrier Structure and Functionmentioning
confidence: 99%